Characterization of the Maize Endosperm Transcriptome and Its Comparison to the Rice Genome - Lai, Jinsheng; Dey, Nrisingha; Kim, Cheol-Soo; Bharti, Arvind K.; Rudd, Stephen; Mayer, Klaus F.X.; Larkins, Brian A.; Becraft, Philip; Messing, Joachim

(untitled) (Genome Research, 2004)
The cereal endosperm is a major organ of the seed and an important component of the world's food supply. To understand the development and physiology of the endosperm of cereal seeds, we focused on the identification of genes expressed at various times during maize endosperm development. We constructed several cDNA libraries to identify full-length clones and subjected them to a twofold enrichment. A total of 23,348 high-quality sequence-reads from 5′- and 3′-ends of cDNAs were generated and assembled into a unigene set representing 5326 genes with paired sequence-reads. Additional sequencing yielded a total of 3160 (59%) completely sequenced, full-length cDNAs. From 5326 unigenes, 4139 (78%) can be aligned with 5367 predicted rice genes and by taking only the “best hit” be mapped to 3108 positions on the rice genome. The 22% unigenes not present in rice indicate a rapid change of gene content between rice and maize in only 50 million years. Differences in rice and maize gene numbers also suggest that maize has lost a large number of duplicated genes following tetraploidization. The larger number of gene copies in rice suggests that as many as 30% of its genes arose from gene amplification, which would extrapolate to a significant proportion of the estimated 44,027 candidate genes of its entire genome. Functional classification of the maize endosperm unigene set indicated that more than a fourth of the novel functionally assignable genes found in this study are involved in carbohydrate metabolism, consistent with its role as a storage organ.